Subcellular localisation of pMEK has a different prognosis in locally advanced head and neck cancer treated with concomitant radiochemotherapy. Issue 1 (December 2016) - Gomez-Millan, J.; Pajares, B.; Perez-Villa, L.; Carnero, A.; Alvarez, M.; De Luque, V.; Rivas, F.; Trigo, J.; Toledo, M.; Alba, E.; Medina, J.
Abstract Background MEK1 (MAP2K1) and MEK2 (MAP2K2) are closely related dual-specificity protein kinases which function by phosphorylating both serine/threonine and tyrosine residues of their substrates ERK1 and ERK2, controlling fundamental cellular processes that include cell growth and proliferation. To investigate the prognostic significance of pMEK expression in the nucleus and cytoplasm among patients with locally advanced head and neck cancer treated with concurrent radiochemotherapy. Methods Immunohistochemistry was performed on the retrieved archival tissue of 96 patients to detect pMEK, p53 and Ki-67. Results Sixty-six percent of patients were positive for pMEK expression in the nucleus and 41 % in cytoplasm. On univariate analysis, high nuclear pMEK was predictive of worse 5y-DFS and 5y-OS, with a trend to significance (26 % vs. 41 %, p = 0.09; 36 % vs. 47 %, p = 0.07). High cytoplasmic pMEK was predictive of better 5-y OS and 5-y DFS outcomes (61 % vs. 27 %, p = 0.01; 46 % vs. 22 %, p = 0.02). On multivariate analysis, low cytoplasmic pMEK and high nuclear pMEK predicted worse DFS and OS (p = 0.01;p = 0.04 andp = 0.02;p = 0.02 respectively). Conclusions Subcellular localisation of pMEK has different prognosis in locally advanced head and neck cancer treated with radiochemotherapy.